Pengujian Beberapa Varietas Cabai Besar (Capsicum annuum L.) Terhadap Lama Periode Inkubasi dan Tingkat Ketahanannya Terhadap Layu Bakteri Ralstonia solanacearum - Rizka Raihanah; Dewi Fitriyanti; Elly Liestiany (www.ulm.ac.id, 2023)
Large chilies (Capsicum annuum L.) are one of the important vegetable commodities. One of the Plant Pest Organisms that causes large chili production to decline is bacterial wilt disease. Bacterial wilt disease in chili cultivation is usually caused by the bacteria Ralstonia solanacearum. Ralstonia solanacearum is a soil-borne pathogen that is able to live in soil without a host. This bacterium has a relatively large number of hosts in the form of horticultural plants, ornamental plants and weeds. This study aims to test five varieties of large chili plants (Capsicum annuum L.) against bacterial wilt disease (Ralstonia solanacearum). Research was carried out at the Phytopathology Laboratory and at the Banjarbaru Agricultural Faculty Experimental Farm. This research used 5 varieties, namely Limosin, Beton F1, Pilar F1, Darmais F1 and Gada Mk F1 with 4 replications. The Limosin variety has the longest incubation period, namely 39 days, while the Pilar F1 and Gada Mk F1 varieties have the fastest incubation period, namely 30 days. The varieties Beton F1, Pilar F1 and Gada Mk F1 show resistant varieties with percentages of 15%, 10% and 5%, while the Limosin variety shows slightly susceptible varieties with a percentage of 50%.